NEOGENE CRUSTAL SHORTENING AND BASIN EVOLUTION IN TUSCANY (NORTHERN APENNINES) - Bonini, Marco; Boccaletti, Mario; Moratti, Giovanna; Sani, Federico (Ofioliti, 2007)
The structural studies carried out in the Northern Apennines during the last decade show that the Neogene tectonic evolution of this area is much more complex than the classical model which proposed a NE-directed shifting of the compressive front followed by lateral extension in the internal zone tied to the development of the Tyrrhenian basin. Recent structural data systematically collected both in the chain and in the sedimentary fill of the hinterland basins, allow us to propose an alternative model for the development of the basins and for the Neogene evolution of the whole Northern Apennines sector. In the central sector of the chain (Tuscan-Romagna Apennines), there is evidence of polyphase thrust reactivations and out-of-sequence thrusting. In the hinterland basins, compressive deformations usually occur in correspondence of thrust ramps and regional unconformities have been found. The timing of both thrust reactivations in the chain and of the major compressive phases affecting the hinterland basins (Radicondoli-Volterra, Baccinello, Velona and Siena-Radicofani basins) well correlates with the periods of magmatic quiescence and with the compressive phases detected in the external sector of the Northern Apennines (Padan-Adriatic foredeep). The presented data allow us to propose that compressive tectonics played a major role in the recent evolution of the Northern Apennines. The mechanism envisaged to explain this tectonic framework has been related to the piggyback emplacement (from the internal toward the external areas) of basement thrusts, that occurred since Miocene. The emplacement of basement thrusts likely caused the reactivation of cover thrusts, giving rise to out-of-sequence thrusting and affecting the development and/or deformation of the hinterland basins. This tectono-sedimentary evolution based on field analysis fits well with the recent reinterpretations of a deep seismic profile (CROP 03 line) hypothesising that basin development was strictly related to crustal shortening. In this frame, the extensional structures have been interpreted either as second-order features accommodating thrusting or as related to the Middle Pliocene and Quaternary extensional phases during which fault-controlled basins locally developed.